Computation of 2, 4 and 2, 3-inverses based on rank-one updates. Issue 1 (2nd January 2018) - Stanimirović, Predrag S.; Katsikis, Vasilios N.; Pappas, Dimitrios
Abstract: Two finite recurrent procedures for computing and -inverses of a matrix are presented. Each of introduced methods exploits certain matrix product which includes the Moore–Penrose inverse of a symmetric matrix and a generalization of the Sherman-Morrison formula to the case of the Moore–Penrose inverse of a symmetrically rank one modified matrix. The computational complexity of the methods is analysed. In the essence, presented representations investigate dual methods with respect to these introduced in [Stanimirović PS, Katsikis VN, Pappas D, Computing 2, 4 and 2, 3-inverses by using the Sherman-Morrison formula, Appl. Math. Comput. 2016;273:584–603].